Menelisik Gerak Zombie Dalam Legislasi Indonesia Atas Cipta - Sarip, Sarip (Faculty of Law, Universitas Muhammadiyah Pontianak, 2023)
Art no. 11/2020 concerning Job Creation is still valid, according to the deadline for the Constitutional Court Decision. During the two years it was ignored as unconstitutional, the articles that had been revoked or amended were reinstated. The principle of lex posterior derogate legi priori, should this principle be passed in order to revive the old rules under the pretext of the principle of lex specialis derogate legi generali. The solution to the problem tries to use zombie science, as an evil consequence of the evaluation of knowledge based on self-interest which has an impact on the possibility of regional autonomy. The discussion posits another point of view, in finding thoughts drawn from the angle of possibility arising from the point of view of zombie science destroying definite theory. The results of other studies show that the results of the study show that there is a potential for injustice to the parties affected by a positive fictitious decision. Noting the similarities in content, form, and function between law and morality, there is a significant difference between these two systems of normative social order. Must consider the law by including morality, moral principles, and political and historical considerations.